Methotrexate Treatment of Newly Diagnosed RA Patients Is Associated With DNA Methylation Differences at Genes Relevant for Disease Pathogenesis and Pharmacological Action - Guderud, Kari; Sunde, Line H.; Flåm, Siri T.; Mæhlen, Marthe T.; Mjaavatten, Maria D.; Norli, Ellen S.; Evenrød, Ida M.; Andreassen, Bettina K.; Franzenburg, Sören; Franke, Andre; Rayner, Simon; Gervin, Kristina; et al. (Frontiers in Immunology, 2021)
Background: Methotrexate (MTX) is the first line treatment of rheumatoid arthritis (RA), and methylation changes in bulk T cells have been reported after treatment with MTX. We have investigated cell-type specific DNA methylation changes across the genome in naïve and memory CD4+ T cells before and after MTX treatment of RA patients. DNA methylation profiles of newly diagnosed RA patients (N=9) were assessed by reduced representation bisulfite sequencing. Results: We found that MTX treatment significantly influenced DNA methylation levels at multiple CpG sites in both cell populations. Interestingly, we identified differentially methylated sites annotated to two genes; TRIM15 and SORC2, previously reported to predict treatment outcome in RA patients when measured in bulk T cells. Furthermore, several of the genes, including STAT3, annotated to the significant CpG sites are relevant for RA susceptibility or the action of MTX. Conclusion: We detected CpG sites that were associated with MTX treatment in CD4+ naïve and memory T cells isolated from RA patients. Several of these sites overlap genetic regions previously associated with RA risk and MTX treatment outcome.